(3GdCHQGQ aj HQi Gdbde hYed GdCMHGQs
(3ChdgG (B:s
(3cJGH GdCHQGQ ai HQi Gdbde hYed GdCMHGQ GYde habfG Gddg JYGdi s
(3BNQgG (B:s
(3aEPG La GUbd Ydi HeG Ubd GdRGL JeJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdRQGYI h GdCYTGHs